Paradise in Antiquity : Jewish and Christian views - Bockmuehl, Markus N. A.; Stroumsa, Guy G. (Cambridge ; New York : Cambridge University Press, 2010)
"The social and intellectual vitality of Judaism and Christianity in antiquity was in large part a function of their ability to articulate a viably transcendent hope for the human condition. Narratives of Paradise - based on the concrete symbol of the Garden of Delights - came to play a central role for Jews, Christians, and eventually Muslims too. These collected essays highlight the multiple hermeneutical perspectives on biblical Paradise from Second Temple Judaism and Christian origins to the systematic expositions of Augustine and rabbinic literature. They show that while early Christian and Jewish sources draw on texts from the same Bible, their perceptions of Paradise often reflect the highly different structures of the two sister religions. Dealing with a wide variety of texts, these essays explore major themes such as the allegorical and literal interpretations of Paradise, the tension between heaven and earth, and Paradise's physical location in space and time"--
Machine generated contents note: 1. Introduction Guy G. Stroumsa; Part I. Paradises of Second Temple Judaism and Christian Origins: 2. The Messiah in the Garden Joachim Schaper; 3. Philo's scholarly inquiries into the story of Paradise Maren R. Niehoff; 4. Paradise in the Biblical Antiquities of Pseudo-Philo Richard Bauckham; 5. Paradise, gardens and the afterlife in the first century CE Martin Goodman; 6. Paradise in the New Testament Grant Macaskill; 7. Quis et Unde? Heavenly obstacles in Gos. Thom. 50 and related literature Simon Gathercole; Part II. Contemporizing Paradise in Late Antiquity: 8. Tertullian and the law of Paradise Sabrina Inowlocki; 9. The language of Paradise: Hebrew or Syriac? Linguistic speculations and linguistic realities in late antiquity Yonatan Moss; 10. The Tree of Life and the turning sword: Jewish biblical interpretation, symbols and theological patterns and their Christian counterparts Menahem Kister; 11. Erotic Eden: a rabbinic nostalgia for Paradise Galit Hasan-Rokem; 12. Augustine on Virgil and Scripture Gillian Clark; 13. Paradise as political theme in Augustine's City of God Emile Perreau-Saussine; 14. Locating Paradise Markus Bockmuehl; Epilogue: a heaven on earth Alessandro Scafi; Bibliography; Index.
Includes bibliographical references (p. 221-247) and index.
Keywords: Paradise; Future life; Paradise -- Judaism; Paradise -- Christianity; Future life -- Judaism; Future life -- Christianity